Analysis of Principal Issues and Key Technologies in Intelligent Perception of Veterinary Drug Circulation and Use Process. (January 2019) - Xing, Liwei; Cheng, Guodong; Sun, Wei; Wu, Jianzhai; Han, Shuqing; Kong, Fantao
Abstract: Through exploring the current research status of veterinary drug circulation and use, the principal issues in the process of veterinary drug circulation and use are discussed. This paper summarizes the application of GSP-based traceability and correlation technology in veterinary drug circulation, package identification aggregation and splitting conversion technology in veterinary drug logistics, real-time perception technology in cold chain transportation of veterinary biological products, and "one-to-one" matching technology, veterinary drugs, livestock and poultry in intelligent perception of veterinary drug circulation and use process.